Indian Secularism : A Social and Intellectual History, 1890-1950 - Tejani, Shabnum (Book collections on Project MUSE., 2008)
Tracing the social, political, and intellectual genealogies of the concepts of secularism and communalism from the late nineteenth century until the ratification of the Indian constitution in 1950, she shows how secularism came to be bound up with ideas about nationalism and national identity.